Religion as culture. Issue 3 (23rd July 2020) - Aranoff, Deena
Abstract: When we understand religion as culture, we can value religion as a many‐thousand year expression of lived human experience with accumulated wisdom. If we ask religion to carry the torch of civil harmony into the election battles, however, religious leaders will have to give up one quite precious thing, namely, the claim to absolute and unchanging truth.